FLORISTIC DIVERSITY AND STRUCTURAL CHARACTERISTICS OF MANGROVE FOREST OF RAJA AMPAT, WEST PAPUA, INDONESIA - Suhardjono Prawiroatmodjo; Kuswata Kartawinata (REINWARDTIA, 2014)
We studied  the floristic compostion and structure of mangrove forests and mangrove species distribution at the Raja Ampat Regency, West Papua  We sampled the forests using (10x10 m) quadrats to record trees and saplings  laid out contiguously along 9 transects of 60 – 450 m long,  stretching perpendicularly from the coastlines or riverbanks to the landward borders. Seedlings were sampled using a 1x1 m subplot nested in each quadrat.  The transects were established on the islands of  Batanta (6), Salawati  (2). and Waigeo (1).  Within quadrats and transects we recorded 17 mangrove species of trees with density of 768 stems/ha and basal area of  37.82 m2/ha and tree height of  10 – 30 m.   Two species possessed  the highest importance value  (IV) , frequency, density and basal area  i.e. Rhizophora apiculata (IV=168.06 %) and  Bruguiera gymnorrhiza (IV=67.18).  They also showed the highest similarity in their distribution,  indicating highest degree of association.  The mangrove at Raja Ampat may, therefore,  be designated as the Rhizophora apiculata-Bruguiera gymnorrhiza Association. Other species with highest degree of distributional similarities but with low densities, basal areas and importance values were Barringtonia racemosa, Excoecaria agallocha, Hibiscus tiliaceus, Inocarpus fagifera,  Lumnitzera littorea and Sterculia shillinglawii,  of which four of them are not  true mangrove species, usually growing on less saline and more solid soils. The floristic composition of the transects in the three islands showed relatively high similarities of about 70 % and at higher similarities the transects in Batanta Island formed four groups, Salawati Island two groups and Waigeo Island one group.The Bray-Curtis polar ordination  resulted in four groups  of transects, which were related to the habitat  conditions and the length of the transects. Species diversity in the islands was very low, where the  Shannon diversity index  ranged  from  0.19 to 0.64 giving  the average  of 0.42. Rhizophora apiculata and Bruguiera gymnorrhiza  were gregenerating well and in the future they will remain dominant.  The mangrove forests of the Raja Ampat Islands by any means should be maintained as green belts and  protected from all kinds of destruction and should be made into conservation areas in order to sustain its ability to provide ecological services  and non-destructive economic benefits.